Rajat Gupta: An American Dream Upturned - A Case Study. Issue 2 (July 2013) - Rawat, Surya Rashmi; Raj, Vignesh; Manoharan, Arvind; Vineet, Shubham
A glittering career of over 35 years whose inspirational story has been a fairy tale to many aspiring management graduates and entrepreneurs across the globe, this case study revolves around the corporate journey travelled by the Indian American businessman, Rajat Gupta . The objective of this case study is to track the rise and fall of one of the most celebrated corporate executives of the present era, tracing his miraculous journey from an orphan in Kolkata to his success at McKinsey & Company through sheer hard work and determination and finally his corporate demise on account of conviction for conspiracy and securities fraud. The case study critically analyses Rajat Gupta through the ups and downs of his corporate career .